Toothbrushing and Access to Dental Services in Peruvian Children - Natalie Hadad-Arrascue DDS; María Claudia Garcés-Elías MBA; Jesús L. Chirinos DrPH (SAGE Publishing, 2023)
Objective. The aim was to determine the association between access to dental services and toothbrushing in Peruvian children under 12 years old. Methods. This was a cross-sectional study with a population of 2021 database of the Demographic and Family Health Survey. Records of children under 12 years old who provided answers about their toothbrushing were included. Variables were evaluated descriptively and followed by a bivariate analysis; multivariate tests were performed using Poisson regression with a multilevel regression analysis. Results. General toothbrushing was 96.32% (n = 34 198), and daily toothbrushing was 88.05% (n = 28 444). Access to dental services was associated with general toothbrushing (aPR: 1.18; 95% CI: 1.14-1.22; P  < .001), daily toothbrushing (aPR: 1.08; 95% CI: 1.04-1.12; P  < .001) and minimum toothbrushing 2 times a day (aPR: 1.12; 95% CI: 1.07-1.17; P  < .001). Conclusion. Access to dental services was associated with general toothbrushing, daily toothbrushing and toothbrushing at least twice a day.